Transport Costs and the Geography of Arbitrage in Eighteenth-Century China - Shiue, Carol H (American Economic Review, 2002)
Trade has been considered a condition for growth and development, a view that might have merits in explaining the rise of the Western world. I use a new data set from archival sources of eighteenth-century China to revisit this question. This analysis suggests previous studies of market integration, which attribute much growth to a reduction in transport costs, have overestimated these effects. I find the overall level of market integration in China was higher than previously thought, and, intertemporal effects are important substitutes for trade. Both factors reduce the importance of trade as a unique explanation for subsequent growth.